Morphology of Microstructures of Oil Components with Increased Stability against Biological Decomposition - A.S. Gordeev; A.A. Shinkarev; A.A. Nesmelov; R.A. Galiev (Учёные записки Казанского университета: Серия Естественные науки)
The electron microscopy study of various types of oil-containing samples (soil polluted by stocktank oil, low-density fraction (< 1.4 g/cm3) of the oily sludge after all stages of the technological scheme of phytoremediation, and arable chernozem exposed to regular pollution by overland runoff from the sites of operational oil wells) has been performed. The transmission electron microscopy has shown the presence of electron-opaque spatially structured organic formations with different morphologies and linear sizes